Non–High-Density Lipoprotein Cholesterol and Apolipoprotein B in the Prediction of Coronary Heart Disease in Men - Pischon, Tobias; Girman, Cynthia J.; Sacks, Frank M.; Rifai, Nader; Stampfer, Meir J.; Rimm, Eric B. (Circulation (New York, N.Y.), 2005)
Background— Apolipoprotein B (apoB) plasma levels reflect the concentration of proatherogenic lipoproteins very low-density lipoprotein and low-density lipoprotein (LDL), whereas non–high-density lipoprotein cholesterol (non–HDL-C) levels reflect the concentration of cholesterol transported by these particles. Methods and Results— The aim of our study was to compare apoB, non–HDL-C, LDL cholesterol (LDL-C), and other lipid markers as predictors of coronary heart disease (CHD) in a nested case-control study among 18 225 participants in the Health Professionals Follow-up Study. Among men who were free of diagnosed cardiovascular disease at the time of blood collection, 266 had nonfatal myocardial infarction or fatal CHD during 6 years of follow-up. Through the use of risk set sampling, control subjects were selected at a 2:1 ratio and matched with regard to age, date of blood collection, and smoking status. After adjustment for matching factors, the relative risk of CHD in the highest quintile compared with the lowest quintile was 2.76 (95% confidence interval [CI], 1.66 to 4.58) for non–HDL-C, 3.01 (95% CI, 1.81 to 5.00) for apoB, 1.81 (95% CI, 1.12 to 2.93) for LDL-C, 0.31 (95% CI, 0.18 to 0.52) for HDL-C, 2.41 (95% CI, 1.43 to 4.07) for triglycerides (all P trend <0.001), and 1.42 (95% CI, 0.86 to 2.32, P trend =0.19) for lipoprotein(a). When non–HDL-C and LDL-C were mutually adjusted, only non–HDL-C was predictive of CHD. When non–HDL-C and apoB were mutually adjusted, only apoB was predictive; the relative risk was 4.18 (95% CI, 1.30 to 13.49; P trend =0.02) for apoB compared with 0.70 (95% CI, 0.21 to 2.27; P trend =0.72) for non–HDL-C. Triglycerides added significant information to non–HDL-C but not to apoB for CHD risk prediction. Conclusions— Although non–HDL-C and apoB were both strong predictors of CHD in this male cohort, more so than LDL-C, the findings support the concept that the plasma concentration of atherogenic lipoprotein particles measured by apoB is more predictive in development of CHD than the cholesterol carried by these particles, measured by non–HDL-C.